2019
DOI: 10.1155/2019/3487607
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory Effects of CXCR5 in the Mice Retina following Ischemia-Reperfusion Injury

Abstract: Object. Retinal ischemia-reperfusion (I/R) injury is a common pathological process in many ophthalmic diseases; there are no effective therapeutic approaches available currently. Increasing evidence indicates that microglia mediated neuroinflammation plays an important role in the retinal I/R injury. In this study, we aimed to investigate the roles of chemokine receptor CXCR5 in the pathological process of retinal I/R injury model. Method. Retinal I/R injury model was established in CXCR5 knockout and wild mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Previous studies showed that CXCR5 −/− mice have more immature neurons in the dentate gyrus, an increase in baseline locomotor activity, and decreased anxiety-like behavior [ 39 ]. CXCR5 −/− mice may also develop retinal degeneration with pathophysiological changes, such as activation of microglia and accumulation of inflammatory cells, loss of ZO-1 indicative of impaired blood-retinal barrier function after ischemia-reperfusion injury [ 51 ]. These changes could conceivably produce major impact on learning and memory, and thus bias the results in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that CXCR5 −/− mice have more immature neurons in the dentate gyrus, an increase in baseline locomotor activity, and decreased anxiety-like behavior [ 39 ]. CXCR5 −/− mice may also develop retinal degeneration with pathophysiological changes, such as activation of microglia and accumulation of inflammatory cells, loss of ZO-1 indicative of impaired blood-retinal barrier function after ischemia-reperfusion injury [ 51 ]. These changes could conceivably produce major impact on learning and memory, and thus bias the results in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that deficiency of CXCR5 leads to abnormalities in the RPE and with the presence of AMD-like phenotypes in mice [5,8,9]. The findings suggest that CXCR5 plays a protective role in RPE cells.…”
Section: Abnormalities Of the Cxcr5-deficient Rpe In Primary Cell Culmentioning
confidence: 73%
“…The RPE cells play a crucial role in the survival and function of the neural retina by maintaining ionic homeostasis at the subretinal space, prevent access of blood components to the neural retina and autoimmune response, which are in part attributed to the formation of the outer blood-retina barrier (BRB) [12]. Our previous studies suggested that CXCR5 signaling plays a protective role in the integrity of RPE cells to prevent the development of AMD-like pathological phenotypes in mice [5,8,9]. Further evidence supports the notion that CXCR5 is required for the homeostasis of RPE cells ( Figure 1A, B, and unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations